2004
DOI: 10.1002/jgm.492
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐containing adenovirus/polyethylenimine transfer complexes effectively transduce dendritic cells and induce antigen‐specific T cell responses

Abstract: Ad/PEI/RNA transfection is an efficient means for generating RNA-transduced DCs and for stimulating antigen-specific T cell responses. Polyadenylation of RNA enhances CD8(+) T cell responses and is essential for CD4(+) T cell responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In our previous work cells were gene-modified and endowed with novel and wanted properties for use in medical therapy [7][8][9][10][11][12][13][14]. The application of such engineered cells is expected to become a routine in future medicine.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work cells were gene-modified and endowed with novel and wanted properties for use in medical therapy [7][8][9][10][11][12][13][14]. The application of such engineered cells is expected to become a routine in future medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmid DNA electroporation was found to be not applicable for tumour antigen loading of DCs because DCs electroporated with antigen plasmid DNA were unable to stimulate T cells in an antigen-specific manner. Inefficient DNA delivery into DCs and ineffective CD4 + and CD8 + T cell stimulation by DNA-transduced DCs have been also reported by the authors' group and others using different transfection systems [43,61]. Thus, electroporation of DCs with RNA is the most powerful method for high transfection efficiency and strong stimulation of T cell responses identified so far.…”
Section: Optimisation Of Rna Transductionmentioning
confidence: 56%
“…These structures increase RNA stability and prevent RNA degradation, as well as mediating the recruitment of the 40S and 60S ribosomal subunits and of eukaryotic translation initiation factors. The authors' group and others studied the effect of RNA-stabilising components, such as the cap structure and the polyA + tail, and found that capping and polyadenylation of RNA is critical for efficient antigen presentation and antigen-specific stimulation of T cells by RNA-transduced DCs [53,61,66]. DCs transduced with capped and polyadenylated RNA most likely produce higher levels of antigen than DCs transduced with uncapped and non-polyadenylated RNA.…”
Section: Optimisation Of Rna Transductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The design of polymeric carriers for such differential display of ODN ligands was based on several considerations. Although positively charged polymers such as poly(ethylene amine) have been widely used as nucleic acid carriers, in order to promote condensation and protection of the nucleic acid, the passage of the nucleic acids through cellular membranes into the cytosolic space is mediated at least in part through the interactions of the positively charged polyplex with the negatively charged cellular membrane[4648]. Such nonspecific interaction of the conjugates with cellular membranes is undesirable in the current studies, as the goal is to probe the role of ODN display in the TLR9-mediated activation of immune cells without complications of interactions with the polymer scaffold.…”
Section: Resultsmentioning
confidence: 99%